Imunologi Human Immunodeficiency Virus (HIV) dalam Kehamilan - Maya Savira (Jurnal Ilmu Kedokteran, 2014)
Human Immunodeficiency Virus can be spread through sexual contact , blood products and vertical transmission ofthe mother to the fetus . The high incidence of HIV / AIDS around the world in women over 15 years old and childrenunder the age of 15 years gives an overview of HIV / AIDS cases in pregnant women likely to have a high incidence.HIV viral RNA viruses belonged to two different types , namely HIV - 1 and HIV - 2 . Most cases are caused by HIV- 1. HIV primarily infects CD4 lymphocytes or T helper ( Th ), the numbers will decrease , as well as the function ofthe immune system will decrease. During pregnancy occurs emphasis on immune cells, with or without HIV infection.Study in France showed no significant progression between the immune system of pregnant women with HIV andnormal pregnant women . T reg on HIV infection in lymphoid tissue accumulated and the number of T reg postpartum was higher in patients with HIV infection compared to HIV- negative . Human Leukocyte antigen - G ( HLA- G ) inhibits cell-mediated immune response and can penetrate the placenta spread of HIV - 1 infection and increasethe risk of vertical transmission . Major histocompatibility complex ( MHC ) encodes HLA - G to inhibit natural killercells ( NK cells) that supports the entry of the virus passes through the placental barrier in HIV- 1 positive pregnantwomen . HIV infection activates CD8 expressing HLA - DR antigen . CD8 immune activation in chronic HIV becomesa factor decreasing CD4 count . The expression of HLA - DR and CD38 on CD8 T lymphocytes that recognize CD4eliminated by HIV infection Total CD8 , CD38 , and HLA - DR is reduced in HIV- positive pregnant women may bea prognostic parameters of immune status.